Electronic cigarettes: A comparison of national regulatory approaches - Rose, Adam (Can J Public Health, 2015)
E-cigarettes have been readily available to global markets since 2004. However, regulations have lagged behind popular use and availability. As policies emerging from national health agencies have an important role to play in shaping consumer health, we examined the existing and upcoming national regulations surrounding e-cigarette availability and use in a convenience sample of English- and French-speaking countries, including Canada, the United States, the United Kingdom, France, Australia and New Zealand. There is substantial international variation in regulatory policies and the extent to which these are enforced. Of the countries considered in this review, the US has regulations that remain the most permissive, whereas those in Canada and New Zealand are the most conservative. However, regulations in Canada, Australia and New Zealand are easily bypassed through Internet imports and lenient enforcement. European health agencies are paving the way for Member States to take appropriate steps to regulate e-cigarettes according to their own jurisdictions. Currently, national regulations of e-cigarettes appear to be ill-defined in terms of shaping the future of e-cigarette availability and use. National regulations should be strengthened to reflect the public health implications of e-cigarettes and to emphasize their difference from consumer products.